2022
DOI: 10.3389/fonc.2022.989258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infection with hepatitis B virus on the survival outcome of diffuse large B-cell lymphoma in the prophylactic antiviral era

Abstract: Patients with lymphoma who are also infected with Hepatitis B virus (HBV) have a poor prognosis. This could be partly explained by the delay or premature termination of anti-tumor treatment because of HBV reactivation. However, there is limited data on the survival outcome of patients HBV-related lymphoma in the era of prophylactic antivirals. Data for 128 patients with HBV surface antigen-positive diffuse large B-cell lymphoma was collected. The median age was 54 years and the ratio of men to women was 1.2:1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
0
0
Order By: Relevance
“… 16 In addition, a study that collected data from 128 patients with HBsAg(+) with DLBCL, all of whom received immunochemotherapy and prophylactic antiviral therapy, found that the prognosis for HBsAg(+) patients was no worse than that for DLBCL patients. 17 Another study showed that approximately 50% of DLBCL patients receiving R-CHOP or CHOP-like chemotherapy had their therapeutic dose reduced due to active HBV infection, while 66.7% had to abandon first-line therapy due to HBV infection. 18 Therefore, in order to improve patient prognoses, early preventive intervention with antiviral drugs should be used for HBV-positive patients with relapsed refractory DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In addition, a study that collected data from 128 patients with HBsAg(+) with DLBCL, all of whom received immunochemotherapy and prophylactic antiviral therapy, found that the prognosis for HBsAg(+) patients was no worse than that for DLBCL patients. 17 Another study showed that approximately 50% of DLBCL patients receiving R-CHOP or CHOP-like chemotherapy had their therapeutic dose reduced due to active HBV infection, while 66.7% had to abandon first-line therapy due to HBV infection. 18 Therefore, in order to improve patient prognoses, early preventive intervention with antiviral drugs should be used for HBV-positive patients with relapsed refractory DLBCL.…”
Section: Discussionmentioning
confidence: 99%